Building the capacity of local partners and government staff on climate smart agriculture technologies and climate change programming. Training Workshop Report - Jalang’o Anyango, Dorcas; Kinyua, Ivy Wambui; Templer, Noel; Wanyonyi, Tabitha; Mwongera, Caroline (2022)
Owing to the increasing impacts of climate change on agriculture and agro-allied sectors, the Alliance of Bioversity International and CIAT organized and facilitated a 4-day workshop under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Project. The workshop aimed to build the capacity of stakeholders, including local partners and government staff in Kenya, on climate-smart agriculture technologies and mechanisms to integrate climate change into their programming.